2001
DOI: 10.1002/1097-0010(200102)81:3<342::aid-jsfa824>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Salmonella reduction in fermented pig feed

Abstract: To protect consumers from Salmonella infection acquired through the consumption of pork meat, it is necessary to eradicate Salmonella from pork. In order to achieve this, the whole pork production chain should be free from Salmonella, including the pigs at the farm. In epidemiological studies it was concluded that the use of fermented feed plays a signi®cant role in the reduction of Salmonella prevalence in pig farms. However, the mechanism of Salmonella reduction in fermented feed is not known. A controlled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…were determined as described by Mossel et al (20). VFA and lactic acid analysis was performed with high performance liquid chromatography (HPLC) as described by van Winsen et al (36). The criteria for the fermented feed were: pH, Ͻ4.5; lactic acid, Ͼ150 mmol/liter; acetic acid, Ͻ40 mmol/liter; butyric acid, Ͻ5 mmol/liter; ethanol, Ͻ0.8 mmol/liter; total lactobacilli, Ͼ9 log CFU ml…”
Section: Methodsmentioning
confidence: 99%
“…were determined as described by Mossel et al (20). VFA and lactic acid analysis was performed with high performance liquid chromatography (HPLC) as described by van Winsen et al (36). The criteria for the fermented feed were: pH, Ͻ4.5; lactic acid, Ͼ150 mmol/liter; acetic acid, Ͻ40 mmol/liter; butyric acid, Ͻ5 mmol/liter; ethanol, Ͻ0.8 mmol/liter; total lactobacilli, Ͼ9 log CFU ml…”
Section: Methodsmentioning
confidence: 99%
“…The acidification of feed by the microbial metabolism may reduce the emptying rate of the stomach (22) and stimulate the secretion of proteolytic enzymes (11). The proliferation of spoilage organisms and food-borne pathogens can be prevented by low pH and high concentrations of lactic and acetic acids (2)(3)(4)38). Lyberg et al (20) found that the pH decreased to approximately 4.0 during the first 3 to 5 days of feed fermentation and that this reduction reduced the levels of enterobacteria in the fermented feed.…”
mentioning
confidence: 99%
“…The association between wetfeeding and lower Salmonella prevalence in swine farms has been reported previously (Farzan et al, 2006;Lo FoWong et al, 2004;van Winsen et al, 2002). Several explanations have been offered, including that during a natural fermentation process in wet feed, the pH is lowered due to the production of lactic acid and acetic acid by lacticacid producing bacteria and the growth of yeasts (which inhibits growth of Salmonella on the feed) (van Winsen et al, 2001) or at least reduces the numbers beyond the detection limit. Gastro-intestinal tract microflora modification with lactic acidproducing bacteria is a mechanism for Salmonella exclusion (Canibe and Jensen, 2003;van Winsen et al, 2002).…”
Section: Resultsmentioning
confidence: 86%